2009
DOI: 10.1007/s00198-009-0970-6
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density at femoral neck is a predictor of increased mortality in elderly Japanese women

Abstract: Our findings suggest that preventive strategies should be considered to increase and maintain high BMD at the femoral neck in elderly subjects not only to prevent osteoporosis and its associated fractures but also probably to reduce mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 44 publications
(54 reference statements)
3
52
0
2
Order By: Relevance
“…(7)(8)(9)(10) However, the majority of studies concerning low BMD and mortality have focused on white populations (9,11) ; a smaller number have included ethnic minorities. (12,13) Some epidemiological studies have also suggested that mineral metabolism biomarkers, especially low serum 25-hydroxyvitamin D (25OHD) concentrations and higher intact parathyroid hormone (iPTH) levels, separately or in combination, are related to mortality among institutionalized older adults (14) and community-dwelling elderly people without primary hyperparathyroidism. (15) Several biological mechanisms have been proposed to explain a possible causal relationship between vitamin D deficiency or elevated PTH and increased mortality risk, especially cardiovascular features, including atherosclerosis, (16,17) left ventricular hypertrophy, (18,19) and arterial stiffness and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…(7)(8)(9)(10) However, the majority of studies concerning low BMD and mortality have focused on white populations (9,11) ; a smaller number have included ethnic minorities. (12,13) Some epidemiological studies have also suggested that mineral metabolism biomarkers, especially low serum 25-hydroxyvitamin D (25OHD) concentrations and higher intact parathyroid hormone (iPTH) levels, separately or in combination, are related to mortality among institutionalized older adults (14) and community-dwelling elderly people without primary hyperparathyroidism. (15) Several biological mechanisms have been proposed to explain a possible causal relationship between vitamin D deficiency or elevated PTH and increased mortality risk, especially cardiovascular features, including atherosclerosis, (16,17) left ventricular hypertrophy, (18,19) and arterial stiffness and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies that have examined the association between mortality and BMD have assumed that there was a linear gradient of risk for death with BMD [5,6] or reported hazard ratios comparing tertiles or quartiles of BMD [7,8,[10][11][12][13][14]. The comparison of quartiles (or quintiles, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Within this age range, there was no evidence of any age dependency, but this does not exclude an important effect at other ages. Other studies have not addressed age-dependent effects [5,[7][8][9][10][11][12][13][14], but it would be important to do so for judging the impact of the effect of BMD-associated mortality on the estimate of fracture probability (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D deficiency is associated with the marked suppression in intestinal Ca absorption and the impairment of Ca balance, which results in low bone mineral content and density. Reduced bone mineral density (BMD) increases the risk of fractures, which significantly contributes to morbidity and mortality of older persons 10,11 .…”
Section: Osteoporosismentioning
confidence: 99%